Amelioration of inflammatory bowel disease by Bifidobacterium animalis subsp. lactis XLTG11 in combination with mesalazine - Ma, Weiwei; Wu, Yanan; Lin, Xinyue; Yang, Liping; Huang, Lili (Frontiers in Microbiology, 2024)
The treatment of inflammatory bowel disease (IBD) remains challenging and significantly impacts both patients and their families. This study evaluated the role of Bifidobacterium animalis subsp. lacti XLTG11 (XLTG11) in combination with mesalazine (5-ASA) in the improvement of IBD. The results demonstrated that the XLTG11+5-ASA group exhibited superior recovery compared to both the XLTG11-only group and the 5-ASA-only group. The XLTG11+5-ASA group significantly reduced myeloperoxidase activity (MPO), attenuated colonic tissue damage, lowered the levels of lipopolysaccharides (LPS) and D-lactic acid (D-LA), and decreased intestinal permeability. Furthermore, it upregulated the mRNA expression of Claudin-1, Occludin, ZO-1, and MUC2, which contributed to the protective effect on intestinal barrier function. Additionally, the XLTG11+5-ASA group significantly increased the levels of anti-inflammatory cytokines while decreasing pro-inflammatory cytokine levels. Notably, treatment with the XLTG11+5-ASA group significantly increased levels of acetic, propionic, and butyric acids, as well as the relative abundance of beneficial bacteria such as Bifidobacterium and Lactobacillus, while decreasing the relative abundance of Enterococcus, Enterobacteriaceae, and Clostridium perfringens. The results indicate that the combination of XLTG11 and 5-ASA was more effective in treating IBD than either treatment alone, significantly improving IBD-related symptoms and providing a scientific basis for future clinical applications.